LA AUSENCIA AMBIGUA: HACIA UN SIGLO SIN INTELECTUALES - Laca Arocena, Francisco A. (Universidad de Costa Rica, 2013)
The article confirms a growing loss of influence from intellectuals in the public eye partially attributed to the changing biographies from the disparaged figure of ‘master’ during the past and conflicted 20th century but, most of all, to the run down of historicisms that many of them served. It is discussed here that these failed historicisms, to which many resources, time and human lives were sacrificed, are probably being replaced by new ‘minor historicisms’ such as the identity nationalisms. Following Karl Popper, it is proposed here to apply in the society a social engineering based on the scientific method of essay-and-error that only truly democratic organizations allow, and finally, it is discussed in favour of benevolence as a laic and no partisan value of moderation from possible excesses in efficacy search in which the social engineering may incur.